2012
DOI: 10.1002/bate.201200042
|View full text |Cite
|
Sign up to set email alerts
|

Großversuche zur Ermüdung von Litzenseilen auf Umlenksätteln für Schrägseilbrücken

Abstract: Large scale fatigue tests of strands on saddle systems for cable-stayed bridges Stay cables made of parallel strands for cable-stayed or extradosed bridges are usually anchored in the pylon or the mast of the bridge. New saddle systems provide the opportunity to support them by saddles that guide the strands continuously from one side of the pylon to the other. While cables made of strands have been tested for fatigue extensively, saddle systems were not yet tested much although the fatigue mechanism occurring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
(1 reference statement)
2
7
0
1
Order By: Relevance
“…A series of fatigue tests were done on steel cables over saddles at TU Berlin (Schlaich et al, 2016). This paper studies the TU Berlin test rig as a saddle system example.…”
Section: Studied Saddle Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of fatigue tests were done on steel cables over saddles at TU Berlin (Schlaich et al, 2016). This paper studies the TU Berlin test rig as a saddle system example.…”
Section: Studied Saddle Systemmentioning
confidence: 99%
“…A team of researchers at TU Berlin has been progressively working on this problem in the last few years. A series of fatigue tests done at TU Berlin to evaluate the fretting fatigue life of steel cables in saddle systems found that the cables usually fail at the contact points where the cables first meet the saddle (Schlaich et al, 2010(Schlaich et al, , 2016; Mohareb et al (2016) stated that this phenomenon occurs because of the irregular contact stress distribution at the zone where the cables first contact the saddle, and compared the analytical solutions and the results of a 2D Finite Element (FE) model of a band bent over a saddle. Mohareb et al (2017) developed a 3D FE model for the contact points between a cable and a saddle to evaluate the fretting fatigue life of the cables.…”
Section: Introductionmentioning
confidence: 99%
“…Dieser Versuchsaufbau ist sehr komplex (Sattel mit zyklischer Verschiebung etc.) und erfordert bei großen Seilen neben hohen Prüflasten einen sehr hohen Platzbedarf . Aufgrund dieser Problematik wurde für die 30‐MN‐Prüfmaschine ein modifizierter Satteltest (Halbsatteltest) am iBMB/MPA entwickelt.…”
Section: Versuchserfahrungen Mit Der 30‐mn‐prüfmaschineunclassified
“…These tests were costly and time‐consuming. Therefore, an alternative smaller version of this setup was designed and used also at TU Berlin 4 . The new setup enabled tests to be done at three saddle radii of 500, 1000, and 1500 mm.…”
Section: Introductionmentioning
confidence: 99%